2021
DOI: 10.3390/ma14195794
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of the Tensile Deformation and Fracture Behavior of Ti–5Al–5Mo–5V–1Cr–1Fe Alloy with Different Microstructures

Abstract: The plastic deformation processes and fracture behavior of a Ti–5Al–5Mo–5V–1Cr–1Fe alloy with bimodal and lamellar microstructures were studied by room-temperature tensile tests with in situ scanning electron microscopy (SEM) observations. The results indicate that a bimodal microstructure has a lower strength but higher ductility than a lamellar microstructure. For the bimodal microstructure, parallel, deep slip bands (SBs) are first noticed in the primary α (αp) phase lying at an angle of about 45° to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This indicates that dislocation slip is the dominant deformation mechanism of the α phase at the applied temperature [22]. Our previous study indicated that pyramidal slip is difficult to take place within the α P phase which is more likely to slip along its basal or prismatic plane at room temperature [23]. In the present study, Figure 10b-d show that prismatic slip ({1100}<1120>) and pyramidal slip ({1101}<1120>) were prevalent in the α P phase compared with basal slip ({0001}<1120>).…”
Section: Activation Of Slip Systemsmentioning
confidence: 95%
“…This indicates that dislocation slip is the dominant deformation mechanism of the α phase at the applied temperature [22]. Our previous study indicated that pyramidal slip is difficult to take place within the α P phase which is more likely to slip along its basal or prismatic plane at room temperature [23]. In the present study, Figure 10b-d show that prismatic slip ({1100}<1120>) and pyramidal slip ({1101}<1120>) were prevalent in the α P phase compared with basal slip ({0001}<1120>).…”
Section: Activation Of Slip Systemsmentioning
confidence: 95%
“…Numerous examples of studies in which material strength investigations and mi fractography research were combined to extend the investigations can be found in contemporary literature [16][17][18][19][20], some of which deal with investigations at different t perature levels. DIC measurement is currently the most important noncontact strain measurement method and is constantly being further developed [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous examples of studies in which material strength investigations and microfractography research were combined to extend the investigations can be found in the contemporary literature [16][17][18][19][20], some of which deal with investigations at different temperature levels.…”
Section: Introductionmentioning
confidence: 99%
“…In the process, the material requirements and the function requirements mutually prompt each other. Titanium alloys have numerous advantages over other metal materials, including low density, high strength, high- and low-temperature resistance, superior corrosion resistance, and good compatibility with composite materials [ 1 , 2 , 3 , 4 , 5 ]. As a result, titanium alloys play an irreplaceable role compared to other metals.…”
Section: Introductionmentioning
confidence: 99%